Manhaj Al-Zahabi dalam Kitab Mizan Al-I'tidal - Isnayanti Isnayanti (Farabi, 2020)
An Opus is certainly influenced by the background of science or education, the environment in which people live and the tendency of the author to produce a separate manhaj. This paper intends to discuss one of the mahjaj in the science of hadith namely al-Z|ahabi. al-Z| ahabi is one of the most well-known hadith critics in evaluating the hadith narrators. There are many works of al-Z | ahabi in the field of hadith, one of which discusses the criticism of sanad is the book of Miza> n al-I'tida> l fi> Naqd al-Rija> l, this book contains narrators who have indications d{a'if and matru> k so this book is often used to ensure the quality of narrators who are accused of lying, d} a'if or matruk.